MANAJEMEN KEPEMIMPINAN DALAM MENINGKATKAN ETOS KERJA ISLAMI KARYAWAN PT. DISTHI MUTIARA SUCI BANYUWANGI PASCA PAILID - Diana Mutmainnah; Syarifuddin (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
Work ethic is becoming increasingly important at this time, due to lack of employee discipline which causes a decreased work ethic, especially after the bankruptcy at PT. Disti Mutiara Suci thus requires a leader to foster employee work ethics again, in this case it is necessary to implement leadership management in improving employee Islamic work ethics and also know what are the inhibiting and supporting factors of employee Islamic work ethics. The results of this study indicate that leadership management in improving the work ethic of post-bankrupt Islamic employees is a leader who does not restrain his employees so that it is easy to foster a post-bankrupt employee work ethic. And leaders better understand karwanan by not leaving the rules that apply in a company. The supporting factors are the applied promotion, trainings, good communication applied by the leader to subordinates, having trust in the subordinates. Whereas the obstacle factor in this case is the lack of smooth access to enter the work location so that the leadership is difficult to directly monitor, lack of professional work of employees and lack of employee loyalty to the company.